The business insurances in the agriculture of selected EU countries - Pawłowska Tyszko, Joanna (Economics of Agriculture, 2010)
The aim of this paper was to present a general situation of the development of agricultural business insurances in the selected EU countries. The Polish case was particularly included In the analysis both the descriptive statistics and tables methods were used. It was assumed that the development of business insurances in the selected EU countries is diversified and depends on the amount of public assistance of a given country to agricultural sector. A great contribution in the agricultural insurance market development (crops and animal farms) in the EU countries can be attributed to state subsidies thanks to which the state can provide financial assistance to agricultural production insurance. It is an important step towards making such insurance policies more popular, giving tangible benefits to the state, insurance companies and the insured themselves. Subsidising the premium by the state or co-financing the costs of reinsurance is a model example of the public private partnership, aiming to cover all the agricultural producers exposed to specific risks with insurance.